circRNA_101277 Influences Cisplatin Resistance of Colorectal Cancer Cells by Modulating the miR-370/IL-6 Axis - Qing Lv; Qinghua Xia; Anshu Li; Zhiyong Wang (Genetics Research)
Background. Colorectal cancer (CRC) is among the most prevalent malignancies globally. Early detection of precancerous lesions through routine colonoscopy has led to a dramatic reduction in CRC-related incidence and mortality among those between the ages of 50 and 70. However, in those where the disease progresses to an advanced stage, chemotherapy remains the primary available treatment option, and the associated 5-year survival rate remains low. The identification of genes associated with CRC chemoresistance would thus be a beneficial approach to identifying novel treatments for this deadly disease. Methods. The expression of circRNA_101277, miR-370, and IL-6 was assessed via qRT-PCR. IL-6 levels were measured with a human IL-6 ELISA kit based on the provided protocols. CRC cellular proliferation and cisplatin IC50 values were quantified via MTT assays. Luciferase assays were used to detect circRNA_101277 and miR-370 binding sites or miR-370 and IL-6 binding sites. Results. circRNA_101277 was increased in CRC tissues compared with control samples. circRNA_101277 overexpression was evident in CRC cells, and knockdown of this circRNA suppressed cellular proliferation and cisplatin resistance in these cancer cells. At a mechanistic level, circRNA_101277 was found to function by sequestering miR-370, thereby upregulating the miR-370 target gene IL-6 and promoting cisplatin resistance via this miR-370/IL-6 axis. Conclusion. In summary, our data highlight circRNA_101277 as a novel driver of CRC cell cisplatin resistance that functions by sequestering miR-370 and thereby enhancing IL-6 expression. These findings suggest that this circRNA_101277/miR-370/IL-6 axis may represent a critical axis of chemoresistance in CRC that can be targeted to diagnose and/or treat this cancer.